Arte e projetos na educação básica: experiências metodológicas na prática docente - COSTA, Francisca da Silva (2024)
This research structures methodological actions in the teaching of Art through the structuring and application of projects that work to stimulate multidisciplinarity. To this end, I used Project Pedagogy and Cultural Pedagogy, as a guideline and, through this methodology, articulate the total participatory involvement of students and teachers, from the elaboration with foundation and engagement that would enable scientific investigation and contribution to social change. The action is based on quantitative quali research by guiding the data subjectively and by projecting the results into the general development of students' education. Thus, their involvement is perceived, but not in a timely manner for measurement. This study shows a considerable number of proposed activities, in the projects I developed in a continuous process of thirteen years of work in the classroom.